北白令海透明胞外聚合颗粒物的含量与来源 - 马丽丽; 陈敏; 郭劳动; 林峰; 童金炉 (2012)
透明胞外聚合颗粒物(TEP)是海水中大量存在的黏性颗粒物质,它对于海洋颗粒物的聚集、有机碳的埋藏、食物网物质的传递、痕量金属的清除与迁出等均起着重要作用。本研究开展了夏季北白令海陆架、陆坡和海盆区透明胞外聚合颗粒物含量和分布的研究。结果表明,北白令海TEP含量介于34~628Mg/M3(XEQ)之间,其中陆架、陆坡和海盆区TEP的平均含量分别为240,145和83Mg/M3(XEQ),整体呈现由陆架向外海降低的趋势。在陆坡和海盆区,TEP含量随着深度的增加而降低,但在陆架近底层水中,观察到TEP高含量的特征,与近底层水高的TSM,POC相对应。TEP与荧光强度、TSM、POC等的关系分析显示,研究海域TEP存在两个来源,其一为海洋上层水体的浮游生物,其主要贡献于陆架上层、陆坡和海盆水体;其二为陆架沉积物的底栖生物,其通过沉积物再悬浮贡献于陆架近底层水。 Transparent exopolymer particles(TEP) are large,sticky particles in marine environments,and play a significant role in particle dynamics,carbon export,food web energy transfer and scavenging of trace metals.Samples were collected from the northern Bering Sea during summer 2010 for measurements of TEP and other hydrographic parameters to examine the abundance,distributions and sources of TEP.Our results showed that TEP concentrations ranged from 34 to 628 mg/m3(Xeq).The averaged TEP concentrations in the shelf,slope and basin were 240,145 and 83 mg/m3(Xeq),respectively,showing a general decrease from the shelf to the basin.In the slope and basin areas,TEP concentrations decreased with the increasing depth.However,high concentrations of TEP were observed in the shelf bottom waters,coincided with the high values of TSM and POC.The correlations between TEP and fluorescence,TSM and POC suggested two sources of TEP in the northern Bering Sea:(1) in situ production from planktons in the upper water column,and(2) benthic biological processes in the sediments.High TEP concentrations in the shelf bottom waters was predominantly derived from sediment resuspension,which may have a potential effect on carbon biogeochemical cycle and scavenging of trace elements in shelf regions. 中国第四次北极科学考察项目;海洋公益性行业科研专项(201105022-4);福建省自然科学基金项目(2009J06026)